1954
DOI: 10.1017/s0022149x00032715
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of the Helminths of Scottish Hill Sheep

Abstract: A survey of the helminths of Scottish hill sheep, made by collecting over seven hundred viscera from sheep which died from disease or accidents on over eighty farms, has shown that worms are the direct or indirect cause of the death of many sheep, and of loss in condition of many more.Infestations of H. contortus increase in incidence and severity in the late spring, but the majority of hill sheep are not infested with it and it is not a serious problem unless lack of herding, bad weather, etc. harm the sheep.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

1975
1975
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(16 citation statements)
references
References 11 publications
2
14
0
Order By: Relevance
“…The large number of nematode parasite species that was identified in the unimproved Soay sheep grazed on natural pastures, without active management intervention, differed from the situation that usually pertains in improved sheep flocks kept on intensively managed grass and clover pastures and subject to active helminth parasite control. In managed flocks, it is commonplace to identify as few as four parasitic nematode species, with seasonal predominance of just one or two (Parnell et al, 1954;Barger, 1985;Boag and Thomas, 1971;Boag and Thomas, 1977) giving rise to diseases referred to as teladorsagiosis, nematodirosis, haemonchosis, or trichostongylosis (Sargison et al, 2007a). By contrast, co-infection with a larger and more diverse range of nematode parasites is pervasive in wildlife (Petney and Andrews, 1998;Lello et al, 2004) and has been shown in feral Soay sheep (Wimmer et al, 2004;Craig et al, 2006), which have not been subject to intensification and management.…”
Section: Discussionmentioning
confidence: 99%
“…The large number of nematode parasite species that was identified in the unimproved Soay sheep grazed on natural pastures, without active management intervention, differed from the situation that usually pertains in improved sheep flocks kept on intensively managed grass and clover pastures and subject to active helminth parasite control. In managed flocks, it is commonplace to identify as few as four parasitic nematode species, with seasonal predominance of just one or two (Parnell et al, 1954;Barger, 1985;Boag and Thomas, 1971;Boag and Thomas, 1977) giving rise to diseases referred to as teladorsagiosis, nematodirosis, haemonchosis, or trichostongylosis (Sargison et al, 2007a). By contrast, co-infection with a larger and more diverse range of nematode parasites is pervasive in wildlife (Petney and Andrews, 1998;Lello et al, 2004) and has been shown in feral Soay sheep (Wimmer et al, 2004;Craig et al, 2006), which have not been subject to intensification and management.…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological surveys of helminth species infection in hill and lowland sheep flocks in northern Britain consistently identify Teladorsagia circumcincta as the most abundant species (Parnell et al 1954 ;Thomas, 1971, 1977 ;Reid and Armour, 1975 a, b;Stear et al 1997 ;Bartley et al 2003). Similarly, T. circumcincta has long been considered the most significant species infecting the feral population of Soay sheep on St Kilda.…”
Section: Introductionmentioning
confidence: 99%
“…Surveys carried out in Great Britain have shown that Trichostrongylus vitrinus is the species of Trichostrongylus most frequently found m the small intestine (PARNELL et al, 1954;CROFTON, 1955CROFTON, , 1957TAYLOR & CAWTHORNE, 1972;REID & ARMOUR, 1975;CORNWELL, 1975). T. vitrinus was considered to be the main cause of helminthiasis in hoggs in Scotland during the winter and spring (PARNELL et al, 1954) and, in association with Cooperia spp., to be the cause°f winter helminthiasis in Iambs in south-west England (CROFTON, 1957). The pathogenicity of this nematode has been investigated experimentally by TAYLOR & PEARSON (1979), SYKES et al, (1979) and COOP et al, (1979).…”
Section: Introductionmentioning
confidence: 99%